2021
DOI: 10.1093/jbcr/irab018
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Simulation Method on Nursing Students’ Burn Patient Care Planning: A Randomized Controlled Trial

Abstract: Background In nursing education, the rate of students to practice for burn patient care is low. Objectives This research was carried out as a single-blind randomized control group intervention trial to determine the effectiveness of simulation method performed using high-fidelity human patient simulator in nursing students’ burn patient care planning. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For instance, one study indicated that competency in measuring blood pressure, pulse rate, and respiration rate could be achieved after five attempts, whereas changing dry dressings and infusing intravenous fluids required six attempts. According to one study, only 22.4% of nursing students demonstrated adequate knowledge in providing initial care for burn victims [ 13 , 14 ]. Another study highlighted that the majority of nurses exhibited poor knowledge and incompetence in burn care practices.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one study indicated that competency in measuring blood pressure, pulse rate, and respiration rate could be achieved after five attempts, whereas changing dry dressings and infusing intravenous fluids required six attempts. According to one study, only 22.4% of nursing students demonstrated adequate knowledge in providing initial care for burn victims [ 13 , 14 ]. Another study highlighted that the majority of nurses exhibited poor knowledge and incompetence in burn care practices.…”
Section: Discussionmentioning
confidence: 99%
“…Methods included handbooks, 16 preceptorship programs, 10,17 education sessions, 18 and simulations. 19,20 Furthermore, interactive learning methods, such as case studies, role playing, and reflective exercises, were highly valued by the participants as an effective means of educational delivery. 10 Environmental scan An environmental scan was completed to determine the availability of formal education for RNs caring for patients with burn injuries, including reviewing the websites of and contacting nurse educators at two teaching hospitals in Atlantic Canada with burn units.…”
Section: Experienced Rns Have Expressed Feeling Unprepared To Assist ...mentioning
confidence: 99%
“…Findings indicated there was moderate evidence from few studies to support a variety of educational methods for RNs providing care to patients with burn injuries. Methods included handbooks,16 preceptorship programs,10,17 education sessions,18 and simulations 19,20. Furthermore, interactive learning methods, such as case studies, role playing, and reflective exercises, were highly valued by the participants as an effective means of educational delivery 10…”
Section: Literature Reviewmentioning
confidence: 99%
“…Simulators, models and phantoms allow for the acquisition and consolidation of technical skills related to manual procedures, e.g., cardiopulmonary resuscitation, catheterization, intubation, insertion of an infusion [ 3 ]. There are many scientific reports confirming that simulation is an effective educational tool in the field of medicine, including nursing [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%